THE EFFECT OF ENTREPRENEURIAL ATTITUDES, INNOVATION AND CREATIVITY ON BUSINESS SUCCESS IN THE GARMENT INDUSTRY (CV. CELBYM AND YEIKO) - Fauzi, Mohamad; Soehari, Tjiptogoro Dinarjo (Dinasti Publisher, 2020)
This study aims to determine the relationship between entrepreneurial attitudes, innovation and creativity on business success. The object of this research lies in the company CV. Celbym and Yeiko are engaged in the garment industry. All variables in the study were calculated using a questionnaire with a 5- point Likert scale of 74 respondents with SPSS 24 software. The technique used in this study was validity test, reliability test, classic assumption test, hypothesis test, multiple regression analysis test and correlation matrix between dimensions. The result show tha entrepreunership, innovation and creativity have a significant effect on business success.